A importância da gestão administrativa na organização hospitalar - D'Ambrosio, Jorge Luiz (2001)
The theories and practical the administrative ones are excellent instruments so that let us can understand the organizational environment. Important to detach the some processes that are submitted to the organizations, so that they can be argued, be analyzed and be reformulated, with the purpose of not becoming exceeded for the fast changes where the world comes crossing. Its the man who becomes the processes of essential changes the survival of the organizations and it he is who evolves together with the transformations for he himself implanted. That way it is that we present this work which looks for to focus the man in its professional environment, raising aspects of its life and participation in the formation processes and continuity of the organizations.